Design, synthesis and decoration of molecular scaffolds for exploitation in the production of alkaloid-like libraries. Issue 11 (1st June 2015) - Craven, Philip; Aimon, Anthony; Dow, Mark; Fleury-Bregeot, Nicolas; Guilleux, Rachel; Morgentin, Remy; Roche, Didier; Kalliokoski, Tuomo; Foster, Richard; Marsden, Stephen P.; Nelson, Adam
Graphical abstract: Abstract: The design, synthesis and decoration of six small molecule libraries is described. Each library was inspired by structures embedded in the framework of specific alkaloid natural products. The development of optimised syntheses of the required molecular scaffolds is described, in which reactions including Pd-catalysed aminoarylation and diplolar cycloadditions have been exploited as key steps. The synthesis of selected exemplar screening compounds is also described. In five cases, libraries were subsequently nominated for production on the basis of the scope and limitations of the validation work, as well as predicted molecular properties. In total, the research has led to the successful synthesis of >2500 novel alkaloid-like compounds for addition to the screening collection (the Joint European Compound Library, JECL) of the European Lead Factory.